Descriptive Data of Patients with Venous Thromboembolism - Gul Ilhan (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2013)
Purpose: This study was designed for collecting descriptive data about diagnosis and treatment of patients diagnosed with venous thromboembolism (VTE) in an university hospital and for reflecting approach to VTE in such a reference hospital in this way. Material and Methods: We evaluated archive records of patients disgnosed with deep vein thrombosis (DVT) and pulmonary thromboembolism (PTE) between 2000 an 2005. Age average of patients was advanced and most of them were women. They had DVT, PTE, DVT and PTE respectively. Most common diagnostic method used for PTE was computed thomogrphy (CT), for DVT was ultrasonography (USG). VTE was diagnosed most frequently in emergency services and policlinics. Most common chronic risk factors for VTE were cancer, heart failure/romathismal cardiac disease, hyperlipidemia/atherosclerosis and obesity. Risk factors spesific to the attacks (or temporary) were immobilization, surgery, pregnancy, taking oral contraseptive drugs and trauma. Results: In patients investigated for hemostatic risk factors, Factor V Leiden, Prothrombin 20210 A , and MTHFR mutations were found respectively. Symptoms and findings of patients admitted with PTE were dyspnea-tachipnea, tachycardia, palpitation, pleural pain, caugh, fever, anginal pain, hemopthysis, diaphoresis and wheezing . Echocardiography gave positive results for the most of PTE cases. D-dimer test was found high sensitive. Treatments during accute attacks were low moleculer weight heparin (LMWH), standart heparin, thrombolytic therapy, surgery, aspirine and vena cava inferior filter placement. Acute term complications were death, bleeding and heparin induced thrombocytopenia. Conclusion: This retrospective study reflects the approach of VTE diagnosis and treatment in a reference hospital and it may guide for prospective studies. [Cukurova Med J 2013; 38(4.000): 610-616]